Change in plasma volume and prognosis in acute decompensated heart failure: an observational cohort study. (September 2016) - Hudson, Sarah R; Chan, Daniel; Ng, Leong L
Objectives: This study aimed to develop an inexpensive, readily available prognostic indicator in acute decompensated heart failure patients to guide management and improve outcome. Prognostic biomarkers for heart failure exist but are expensive and not routinely performed. Increasing plasma volume has been associated with worse outcomes. Setting: UK University Teaching Hospital. Design: Observational Cohort study. Participants: 967 patients with acute decompensated heart failure. Methods: Haemoglobin and haematocrit were measured at admission and discharge and were used to calculate the plasma volume change using the Strauss-Davis-Rosenbaum formula. Main outcome measures: Endpoints were death and the composite of death and/or heart failure hospitalisation. Change in plasma volume was added to ADHERE scoring to determine predictive value. Results: During follow-up, 536 died and 626 died or were hospitalised with heart failure. Multivariable Cox models showed change in plasma volume was an independent predictor of mortality (hazard ratio (HR) [95% confidence interval (CI)]: 1.150 [1.031–1.283], p  = 0.012) and death or heart failure hospitalisation (HR: 1.138 [1.029–1.259], p  = 0.012). Kaplan–Meier analysis of change in plasma volume tertiles for outcome measures showed significant difference for the top tertile compared to the lower two. Multivariable analysis of change in plasma volume with ADHERE scoring showed change in plasma volume change remained an independent predictor of death (HR: 1.138 [1.026–1.261], p  = 0.015) and death or heart failure hospitalisation (HR: 1.129 [1.025–1.243], p  = 0.014). Conclusions: Change in plasma volume over an admission can be used for prognostication and adds value to the ADHERE score. Change in plasma volume can be easily and inexpensively calculated from routine blood tests. Clinically, this may facilitate targeted treatment of acute decompensated heart failure patients at greatest risk.